Application of a stage based motivational interviewing approach to adolescent smoking cessation: The Transtheoretical Model-based study - (:unkn) unknown (ELSEVIER IRELAND LTD, 2008)
Objective: To evaluate the results of stage-based motivational interviewing (MI) efforts to help adolescents quit smoking using the three constructs of Transtheoretical Models (TTM). The validity of Turkish translations of two key scales was also assessed. Methods: A methodological and single group pre-post test study design was utilized. 275 adolescent smokers from one high school were recruited for validation of the scales and 60 of them participated in MI intervention. Change in smoking stage, interpretation of pros and cons of smoking, temptations, and smoking status were measured prior to the intervention, and follow-up was conducted at 3 and 6 months after intervention. Results: The scales showed adequate reliability and validity for use in Turkish adolescent. Of the MI participants, 40% and 55% had made positive movements in stage at 3 and 6 months, respectively. The interpretations of the cons of smoking significantly increased and temptations dropped toward the action stage at 3 months, and pros of smoking and temptations decreased at 6 months consistently with TTM. The percentages of those who had quit smoking at 3 and 6 months were 18.3% and 33.3% respectively. Conclusion: A modest, short-term benefit of the intervention was provided to students towards stopping smoking and positive movement in stages was apparent. Practical implications: Using the MI principles in specific stages based on TTM, health care providers can influence and empower adolescent smokers positively for quitting smoking. (c) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: smoking cessation; motivational interviewing; transtheoretical model; Turkish adolescents; DECISIONAL BALANCE; TEMPTATIONS; PREVENTION; VALIDATION; BEHAVIOR; TRIAL